Modulation of Wolframin Expression in Human Placenta during Pregnancy: Comparison among Physiological and Pathological States. (23rd January 2014) - Lucariello, Angela; Perna, Angelica; Sellitto, Carmine; Baldi, Alfonso; Iannaccone, Alessandro; Cobellis, Luigi; De Luca, Antonio; De Falco, Maria
Abstract : The WFS1 gene, encoding a transmembrane glycoprotein of the endoplasmic reticulum called wolframin, is mutated in Wolfram syndrome, an autosomal recessive disorder defined by the association of diabetes mellitus, optic atrophy, and further organ abnormalities. Disruption of the WFS1 gene in mice causes progressive β -cell loss in the pancreas and impaired stimulus-secretion coupling in insulin secretion. However, little is known about the physiological functions of this protein. We investigated the immunohistochemical expression of wolframin in human placenta throughout pregnancy in normal women and diabetic pregnant women. In normal placenta, there was a modulation of wolframin throughout pregnancy with a strong level of expression during the first trimester and a moderate level in the third trimester of gestation. In diabetic women, wolframin expression was strongly reduced in the third trimester of gestation. The pattern of expression of wolframin in normal placenta suggests that this protein may be required to sustain normal rates of cytotrophoblast cell proliferation during the first trimester of gestation. The decrease in wolframin expression in diabetic placenta suggests that this protein may participate in maintaining the physiologic glucose homeostasis in this organ.